2018
DOI: 10.1007/s00405-018-4930-7
|View full text |Cite
|
Sign up to set email alerts
|

On the accuracy of cochlear duct length measurement in computed tomographic images

Abstract: The program Comet was successfully used to accurately measure the length of the cochlea models in clinically available imaging. The lower image quality of patient scans reduced the precision of the measurement. Estimations using the A value are a quicker alternative for averagely sized cochleae in cases where the lack of accuracy is tolerable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…A general problem with manual measurements of the basal turn parameters is the inter- and intra-user variability 20,21 : with the proposed approach, the user is still required to manually measure A and B. Rivas et al 20 investigated the variability in manual A value assessments and found mean absolute deviations of 0.22 mm to an automated reference approach. In case of average values A = 9.04 mm and B = 6.33 mm, 8 this mean variability would yield deviations of the BTL (according to equation 1) up to 0.7 mm.…”
Section: Discussionmentioning
confidence: 99%
“…A general problem with manual measurements of the basal turn parameters is the inter- and intra-user variability 20,21 : with the proposed approach, the user is still required to manually measure A and B. Rivas et al 20 investigated the variability in manual A value assessments and found mean absolute deviations of 0.22 mm to an automated reference approach. In case of average values A = 9.04 mm and B = 6.33 mm, 8 this mean variability would yield deviations of the BTL (according to equation 1) up to 0.7 mm.…”
Section: Discussionmentioning
confidence: 99%
“…A landmark was finally set every 30° to 60°. 14 , 15 The whole enrolled cochlea is presented by the software in an additional window. Herein, the CDL (A to C) and the 2TL (A to B; Figure 1 , D and D ′ ) were measured in millimeters.…”
Section: Methodsmentioning
confidence: 99%
“…Eight (13%) studies employed direct histology, 10 (15%) employed indirect methods, 37 (57%) employed spiral coefficients, and 10 (15%) used 3D reconstructions. In addition, three studies measured the LW length and "A" values, 29,32,68 whereas three studies measured OC length and "A" values. 11,34,64…”
Section: Study Characteristics and Summary Measuresmentioning
confidence: 99%